The 4th St. Gallen EORTC Gastrointestinal Cancer Conference: Controversial issues in the multimodal primary treatment of gastric, junctional and oesophageal adenocarcinoma. (May 2019) - Lutz, Manfred P.; Zalcberg, John R.; Ducreux, Michel; Adenis, Antoine; Allum, William; Aust, Daniela; Carneiro, Fatima; Grabsch, Heike I.; Laurent-Puig, Pierre; Lordick, Florian; Möhler, Markus; Mönig, Stefan; et al.
Abstract: Multimodal primary treatment of localised adenocarcinoma of the stomach, the oesophagus and the oesophagogastric junction (AEG) was reviewed by a multidisciplinary expert panel in a moderated consensus session. Here, we report the key points of the discussion and the resulting recommendations. The exact definition of the tumour location and extent by white light endoscopy in conjunction with computed tomography scans is the backbone for any treatment decision. Their value is limited with respect to the infiltration depth, lymph node involvement and peritoneal involvement. Additional endoscopic ultrasound was recommended mainly for tumours of the lower oesophagogastric junction (i.e. AEG type II and III according to Siewert) and in early cancers before endoscopic resection. Laparoscopy to diagnose peritoneal involvement was thought to be necessary before the start of neoadjuvant treatment in all gastric cancers and in AEG type II and III. In general, perioperative multimodal treatment was suggested for all locally advanced oesophageal tumours and for gastric cancers with a clinical stage above T1N0. There was consensus that the combination of fluorouracil, folinic acid, oxaliplatin and docetaxel is now a new standard chemotherapy (CTx) regimen for fit patients. In contrast, the optimal choice of perioperative CTx versus neoadjuvant radiochemotherapy (neoRCTx), especially for AEG, was identified as an open question. Expert treatment recommendations depend on the tumour location, biology, the risk of incomplete (R1) resection, response to treatment, local or systemic recurrence risks, the predicted perioperative morbidity and patients' comorbidities. In summary, any treatment decision requires an interdisciplinary discussion in a comprehensive multidisciplinary setting. Highlights: Summary report of the expert consensus discussion and vote focussed on the primary treatment of gastric and gastro-oesophageal adenocarcinoma. Expert consensus. EUS needed in AEG II/III. Laparoscopy in all gastric cancers and AEG II/III. FLOT regimen standard in gastric cancer.